DESAIN DAN IMPLEMENTASI ALGORITMA PEMBACAAN SENSOR KAPASITIF PADA SISTEM MONITORING GREENHOUSE DAN FERTIGASI BUAH MELON - Mochamad Darius Evan Hananta; Eka Maulana; Akhmad Zainuri (Jurnal Mahasiswa TEUB, 2022)
Crop failure due to high rainfall is a threat to farmers. One solution to overcome this problem is to cultivate melons in a greenhouse. However, this can result in a significant increase in temperature so that the soil in the planting medium dries quickly. In this study, an algorithm was implemented to control the readings of dissolved water content in the planting medium by non-invasive capacitive sensor pieces which were carried out alternately using a decoder, as well as reducing reading noise using the Kalman Filter algorithm. The algorithms designed include reading sensor data every 50 ms, changing each capacitive sensor plate so that it can act as an excitation source, sensing element, and shield in turn, reducing noise reading from the sensor, sending sensor reading data from Arduino Nano to ESP32, receiving and parsing the data according to the data sent by the Arduino Nano, and turning on or off the fertigation system according to the data obtained. Based on the test results showed that the water content read on the capacitive sensor without planting media